2022
DOI: 10.1186/s12877-022-03208-y
|View full text |Cite|
|
Sign up to set email alerts
|

Equipment-free, unsupervised high intensity interval training elicits significant improvements in the physiological resilience of older adults

Abstract: Background Reduced cardiorespiratory fitness (CRF) is an independent risk factor for dependency, cognitive impairment and premature mortality. High-intensity interval training (HIIT) is a proven time-efficient stimulus for improving both CRF and other facets of cardiometabolic health also known to decline with advancing age. However, the efficacy of equipment-free, unsupervised HIIT to improve the physiological resilience of older adults is not known. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 75 publications
(84 reference statements)
1
15
0
Order By: Relevance
“… 26 , 48 , 49 Total lean mass was not significantly changed after WB-HIIT. This result is in agreement with previous studies showing mitigated effects of supervised 44 , 46 , 48 , 49 , 50 and home-based 26 , 27 , 30 WB-HIIT on total lean mass.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“… 26 , 48 , 49 Total lean mass was not significantly changed after WB-HIIT. This result is in agreement with previous studies showing mitigated effects of supervised 44 , 46 , 48 , 49 , 50 and home-based 26 , 27 , 30 WB-HIIT on total lean mass.…”
Section: Discussionsupporting
confidence: 93%
“…The VO 2 peak improvement after WB-HIIT is consistent with previous studies using either supervised 44 , 45 , 48 , 49 , 50 , 58 , 59 , 60 or home-based WB-HIIT. 26 , 28 , 30 The slight increase observed for VO 2 peak (5%) could be due to the short time spent at high intensity (see Table 3 ). This is in line with a recent study showing that oxygen consumption is lower during WB-HIIT compared to a running HIIT with a similar exercise to rest ratio.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…After publication of this article [ 1 ], the authors reported that the wrong Supplementary file was originally published with this article; it has now been replaced with the correct file.…”
mentioning
confidence: 99%